Closed expressions for Lie algebra invariants and finite transformations - Aldrovandi, R. [UNESP]; Barbosa, A. L. [UNESP]; Freitas, L. P. [UNESP] (Springer Nature, 1997)
A simple procedure to obtain complete, closed expressions for Lie algebra invariants is presented. The invariants are ultimately polynomials in the group parameters. The construction of finite group elements requires the use of projectors, whose coefficients are invariant polynomials. The detailed general forms of these projectors are given. Closed expressions for finite Lorentz transformations, both homogeneous and inhomogeneous, as well as for Galilei transformations, are found as examples.